Pitfalls in the Diagnosis of Acute Rheumatic Fever - Zareen, S; Mahmud, RS; Uddin, SN; Ahmed, S; Choudhury, KN (Cardiovascular Journal, 2012)
DOI: http://dx.doi.org/10.3329/cardio.v4i1.9394 Cardiovasc. J. 2011; 4(1): 75-79